The Long Non-Coding RNA HOXC-AS3 Promotes Glioma Progression by Sponging miR-216 to Regulate F11R Expression - Li, Yongshuai; Peng, Lu; Cao, Xianwen; Yang, Kun; Wang, Zhen; Xiao, Yong; Xiao, Hong; Qian, Chunfa; Liu, Hongyi (Frontiers in Oncology, 2022)
HOXC cluster antisense RNA 3 (HOXC-AS3) is a long noncoding RNA (lncRNA) that plays a crucial role in various tumors; nevertheless, its role in glioma and its mechanism have not been completely elucidated. In this research, we discovered that HOXC-AS3 was over-expression in glioma cells and tissues and was associated with prognosis. Next, we determined that HOXC-AS3 targeted miR-216 as a sponge and that the F11 receptor (F11R) was the target of miR-216 by online databases analysis, qRT–PCR, and luciferase reporter assay. In addition, the rescue experiments confirmed that HOXC-AS3 regulated the expression of F11R by competitively binding miR-216 and functioning as a competing endogenous RNA (ceRNA). The intracranial glioblastoma mouse model suggested that HOXC-AS3 could promote glioma malignant progression in vivo. In summary, our study shows that the HOXC-AS3/miR-216/F11R axis plays an important role in the malignant progression of glioma, and may provide new ideas for the treatment of glioma.